Godność człowieka i bioetyka - Bołoz, Wojciech (Horyzonty Wychowania, 2017)
Eighteenth-century declarations of human rights referred tothe Creator (the American Declaration of Independence), or theHighest Being (the French Declaration of Human Rights) as theirguarantors. Progressing secularization of politics and culturemade the theoreticians of human rights turn to human dignity asthe value constituting the source of their being binding. Humandignity may be justified in a religious way (man has a specialstatus, since he is created in God’s own image), or in a purelyrational way (the basis for a special position of man in the worldis his rationality and ability to choose freely). Therefore, humandignity has become a universal value and may serve a point ofreference for supporters of various world views. Special importancehuman dignity and his rights have nowadays in the systemof international law and in bioethics. The last one protects healthand life of individuals in the cases of medical interventions,especially at the beginning and at the end of human life.